Solar Energy : Pergamon International Library of Science, Technology, Engineering and Social Studies. - Messel, H. (Elsevier Science, 1975)
Nine lectures concerning specialized aspects of solar energy such as thermal conversion, the nature of solar energy, and heat transfer and storage.